Securitization, housing market and banking sector behavior in a stock-flow consistent model - Olimpia Fontana; Antoine Godin (Kiel Institute for the World Economy (IfW), 2013)
This paper focuses on the different balance sheet management behavior of private banks and worker households, when assets are traded in the market. The authors take into consideration the securitization process, through which mortgage loans to households are converted into tradable securities which are held by investment banks in order to make profits. The demand for deposits by speculative households and realized capital gains on selling of mortgage-backed securities in the secondary market produce an inflation balloon in security markets, even though the authors apply the Basel III agreements to private banking behavior.
Keywords: E12; G11; E44; 330; securitization; stock-flow consistent modelling; active banking